SISTEM KENDALI TERJARING POSISI MOTOR DC BERBASIS MIKROKONTROLER ATMEGA 16 - , WAHYU AJI EKO P A; , Muhammad Arrofiq S.T., M.T., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Automation is a very popular choice in technology for acquiring practical work system and efficiently in order to get the desired results. In industry world, automation was used as mechanical devices such as DC motor to facilitate people in work. In most industries, process controls are still carried out manually, so it needed a system of netted for control. One of the devices of control automation system that can perform is ATmega16 microcontroller. Dc motor position control system via Ethernet network requires the ATmega16 microcontroller which has an internal 8-bit ADC and PWM module also WIZ812MJ Ethernet module attached. With the increased module Ethernet, control systems netted made can be run successfully. Due to system testing result, the position of dc motor can be controlled via Ethernet at round 0-270 degree rotation with response time 14.778 ms/degrees.